In vitro maturation of oocytes: effective alternative in assisted reproduction - Tominaga, Luis Vargas (2013)
Objectives: To determine the effectiveness of in vitro maturation (IVM) of oocytes in assisted reproduction. Design: Descriptive study. Setting: Centro de Fertilidad y Ginecología del Sur (CFGS), Cusco, Peru. Participants: Women with diagnosis of infertility. Interventions: In eight women we performed IVM of oocytes, followed by ICSI, culture and vitrification of embryos. Thereafter, patients’ endometrium was prepared and the embryos were thawed and transferred. Main outcome measures: Maturation of oocytes, fertilization, clinical pregnancy and implantation rates. Results: Maturation of oocytes rate was 82.1%, fertilization rate 95.7%, clinical pregnancy 62.5% and implantation rate 29.4%. Conclusion: IVM of oocytes is an effective alternative in assisted reproduction. Key words: In vitro maturation of oocytes, in vitro fertilization, intracytoplasmic sperm injection.